Rare Intrasellar Arachnoid Cyst Distinguishing From Other Benign Cystic Lesions and its Surgical Strategies. Issue 5 (July 2019) - Chen, Binghong; Miao, Yifeng; Hu, Yaomin; Liao, Yu; Tu, Mei; Yang, Xi; Qiu, Yongming
Abstract : Abstract: The study reported a case of an intrasellar arachnoid cyst with visual disturbances as the main symptom. Arachnoid cyst is a common intracranial benign space-occupying lesion, but rarely seen in intrasellar region with less than 100 cases reported available in English language literature. Therefore, it is still controversial about the diagnosis and treatment of such patients. This article reviewed previous literature and discussed the differential diagnosis and surgical strategies of intrasellar arachnoid cyst in combination with our own case.